Assessment of Prescription Patterns in Hypertensive and Diabetic Patients Visiting Private Tertiary Care Hospital of Dharan Municipality, Nepal (Sunsari Technical College Journal, 2016)
This study was conducted to assess the drug prescribing trend of anti-hypertensive and hypoglycemic agents in hypertensive and diabetic patients in tertiary care private Hospital. The study was prospective, cross-sectional and observational study. A total of 100 prescriptions were recorded. 56% were males as compared to 44% females. The age group of the patients varied from 30 to 90 years with majority individual above 50 years of age. 59% patients were hypertensive; 26% patients were diabetic and 15% had both the diseases. For the treatment of HTN, both mono-therapy and combination therapy were followed. In mono-therapy, amlodipine was most commonly prescribed followed by losartan. In combination therapy, a two-drug combination consisting of calcium channel blockers (amlodipine) and diuretics (furosemide /hydrochlorothiazide) were given to the majority of patients, followed by Diuretics and Angiotensin receptor blocker combination. Among diabetic hypertensive, 66.67% of patients were treated with single anti-hypertensive drug and 33.35% of patients were treated with anti-hypertensive drug combinations with oral hypoglycemics. This study showed that calcium channel blockers were the most prescribed antihypertensive agents while biguanides were the mostly prescribed among anti-diabetic agents. Combination therapy was observed in a high percentage of prescriptions in hypertensive patients. Prescribing pattern among antihypertensive showed some dubitable adherences to existing evidence-based JNC guidelines.Sunsari Technical College Journal 2015, 2(1):44-47